The Effect Of Surface Modification Of Multi-Walled Carbon Nanotubes On Properties Of Silicone Rubber Composites - Chua , Tze Ping (2010)
In the present study, silicone rubber type poly(dimethylsiloxane) (PDMS) was chosen as a matrix for Thermal Interface Materials (TIM) due to its ease of processing, inert to chemical attack, non-toxic and high thermal stability. Two types of modified multi-walled carbon nanotubes (MWNTs), which are diphenylcarbinol modified MWNTs (D-MWNTs) and silanized diphenylcarbinol modified MWNTs (SD-MWNTs) were produced by chemically treatment. D-MWNTs were prepared by one electron reduction of benzophenone by potassium metal and SD-MWNTs were prepared by treated D-WMNTs with 3 aminopropyltriethoxysilane (3APTES).